THE MODELS TO PRESENT THE EVALUATING MEANING IN UNISON DIALOGUE (Proceedings of Southern Federal University. Philology, 2012)
Boiko A.K.Keywords: unison dialogue, evaluating predicate, perspective evaluation, positive and negative connotation.The dialogical interaction presupposes the evaluation of people, events and situations. In spontaneous dialogical communication we consider evaluation as possible psychological structures lying in the core of the speaker’s speech behaviour in a particular context. The article analyses the model which combines the evaluating predicate with components it or that and is actualized before formulating the assessing situation. The model is considered to be the introduction of the assessing situation. The evaluating predicate introduces the perspective evaluation. It presupposes modeling the assessing situation in the further course of spontaneous dialogue.